Studying the Costs of Fibre Deployment in Fixed Broadband Access Infrastructure: Evidence from the UK's National Needs Assessment - Edward J. Oughton (International Telecommunications Society (ITS), 2016)
There has been a concerted effort in recent years to undertake more strategic, long-term, and cross-sector assessment of national infrastructure. This paper reflects on the assessment of fixed broadband within the recent National Needs Assessment, which aims to identify options for meeting the UK's infrastructure `needs' up to 2050. It establishes the future `need' for different levels of fixed broadband connectivity and how much investment is required to rollout infrastructure to meet different regional coverage and capacity levels. Two key technologies are initially assessed here using a cost modelling approach, including Fibre-To-The-Premises (FTTP) utilising a Gigabit Passive Optical Network and FTTP utilising a Point-To-Point fibre connection. The results show the aggregate investment required to deliver different levels of fixed broadband access to different proportions of the population. The costs raise linearly for delivery to premises in urban areas, with total urban coverage by FTTP using a Gigabit Passive Optical Network costing 14.1 billion and FTTP using a Point-To-Point network costing 17 billion. The costs for rural and remote areas begin to rise sharply, to the extent that deployment of these technologies to the final third of premises could cost almost the same amount as deployment to the first two thirds of premises in urban areas. Deployment to rural and remote areas was estimated to cost 13.7 billion for FTTP using a Gigabit Passive Optical Network and 15.8 billion for FTTP using a Point-To-Point network. Total FTTP coverage using a Gigabit Passive Optical Network costs 27.7 billion, whereas FTTP coverage using a Point-To-Point network costs 32.8 billion. The largest aggregate investment is required in the South East, North West and East of England, due to their large population sizes. Across these technologies the lowest average marginal cost per premises was in London for urban areas, Scotland for rural areas, and Wales for remote areas.
Keywords: 330